Effect of lullaby on volume, fat, total protein and albumin concentration of breast milk in premature infants' mothers admitted to NICU: a randomized controlled trial - Somayeh SefidHaji; Parvin Aziznejadroshan; Mohsen Haghshenas Mojaveri; Hossein-Ali Nikbakht; Durdi Qujeq; Seyedeh Roghieh Jafarian Amiri (BMC, 2022)
Abstract Background Listening to music can reduce or manage stress, fatigue, and accompanying symptoms in mothers. Music increases oxytocin secretion which affects breast milk. This study aimed to examine the effect of lullaby on volume, fat, total protein and albumin concentration of breast milk in mothers of premature infants admitted to the NICU. Methods This clinical trial was performed on 100 primiparous mothers whose premature infants were hospitalized in the NICU of Ayatollah Rouhani Hospital from January 2020 to December 2020. Using block randomization method, the participants were divided into three groups: control (A), playing lullaby for mother (B) and playing lullaby for a mother while holding a photo of her own baby (C). The mothers of the intervention groups listened to lullabies through headphones for 30 minutes every morning for 6 days. On the first and the sixth day of birth, the volume of breast milk (ml) and two milliliters of breast milk samples of all three groups were measured and compared in terms of fat, albumin concentration and total protein (mg/DL). ANOVA, Paired T-Test and ANCOVA model (the included variables were: basic value of dependent variable, group type, Maternal age, Birth weight, Gestational age and Maternal weight) was used for analytical statistics. Results The difference between the mean compositions of breast milk before and after the intervention in three groups of A, B and C: in terms of the breast milk volume were 66.33 ± 4.80, 71.30 ± 4.18 and 75.91 ± 6.80 ml; in terms of triglyceride level was 177.84 ± 50.57, 210.72 ± 34.55 and 224.17 ± 12.97 mg/DL, cholesterol level was 14.57 ± 3.70, 21.96 ± 3.82 and 26.26 ± 5.16 mg/DL, albumin concentration was 0.90 ± 0.30, 1.22 ± 0.19 and 1.46 ± 0.28 mg/DL and total protein level was 1.61 ± 0.61, 2.20 ± 0.57 and 2.72 ± 0.30 mg/DL. Finally, the results of ANCOVA analysis for the effects of the intervention, taking into account the baseline values, showed that the intervention was effective and had the greatest effect on cholesterol levels. Conclusion In this small trial, there was a statistically significant association between trial arm and biochemical composition of breastmilk though further studies are needed to see if these changes result in meaningful clinical outcomes to the infant. Trial registration IRCT, IRCT20191114045439N1. Registered 14 January 2020- prospective, https://en.irct.ir/trial/43671